Pengaruh Metode Struktural Analitik Sintetik (SAS) Terhadap Kemampuan Membaca Permulaan Mata Pelajaran Bahasa Indonesia Siswa Kelas 1 SD - Sari, Resi Maya; Armariena, Dian Nuzulia; Rizhardi, Rury (Institut Teknologi Pendidikan Indonesia, 2022)
Beginning reading is a learning process that is usually carried out in grades I and II of elementary school which is given as the basis for further reading learning, starting with the introduction of letters as symbols of simple language sounds and focusing on aspects of accuracy in adjusting the writing and sentences you want to read. In this study, there is an effect of the Structural AnalyticalSynthetic (SAS) method on the ability to read the beginning of the Indonesian subject of 1st grade elementary school students. This study aims to determine whether there is an effect of Synthetic Structural Analytical Methods (SAs) on the Beginning Reading Ability of Indonesian LanguageSubjects in Class 1 SD IT Kamiliyah Palembang. The research method used is the One Group Pretest Posttest Design method. The results of the research conducted by the author are by showing the hypothesis test t_count = 4.025 > t_table = 2.109 with a significant value <0.05 thenH_0 is rejected, meaning that